Effect of Mesenchymal Stromal Cells of Different Origin on DNA Fragmentation in Rat Hippocampal Neuronal Nuclei After Ischemia-Reperfusion - Konovalov, Serhii; Moroz, Vasyl; Yoltukhivsky, Mykhaylo; Husakova, Iryna; Deryabina, Olena; Tochilovskyi, Albert; Kordium, Vitalii (Innovative Biosystems and Bioengineering, 2025)
Background. The treatment of cerebral blood circulation disorders remains a pressing issue due to their prevalence in the elderly. Brain tissue ischemia caused by such disorders leads to necrotic and neuroapoptotic changes. To mitigate neuroapoptosis in the ischemic zone during the subacute period of the process, neuroprotectors are used. In recent years, the neuroprotective properties of mesenchymal stromal cells (MSCs) have been actively studied. Objective. To compare effect of MSCs of different origin and the cell lysate of human MSCs from Wharton's jelly (hWJ-MSC) on neuroapoptotic changes in the hippocampus of the rat brain after ischemia-reperfusion (IR). Methods. A 20-minute bilateral transient IR of the internal carotid arteries was performed on 165 four-month-old male Wistar rats. Following IR modeling, MSCs derived from hWJ-MSCs, as well as human and rat adipose tissue, were injected intravenously into the femoral vein of the rats. Other groups of rats received intravenous injections of fetal rat fibroblasts and cell lysate from hWJ-MSCs. Only an intravenous injection of physiological solution was administered to the control group of rats. The level of DNA fragmentation in the nuclei of hippocampal neurons on the 7th day after IR was assessed via flow cytometry. Results. Experimental IR caused a 4.9-fold increase in the level of fragmented DNA in the operated rats compared to the sham-operated animals. The use of MSCs of various origins and hWJ-MSC lysate reduces the intensity of DNA fragmentation in the nuclei of rat hippocampal neurons, with the most pronounced effects observed in groups treated with rat fetal fibroblasts (by 4.8 times), human adipose tissue MSCs (by 2.5 times), and hWJ-MSC cell lysate (by 2 times). Conclusions. A persistent focus of necrotic and apoptotic death of neurons in the hippocampus of rats is formed after experimental 20-minute IR of rats' brain, as evidenced by increased levels of fragmented DNA. Intravenous transplantation of MSCs of various origin and cell lysate from hWJ-MSC demonstrated a significant effect in the IR model: neurodestruction and neuroapoptosis at the area of the ischemic brain damage get less intensive. MSCs derived from human adipose tissue demonstrated superior neuroprotective potential compared to rat adipose tissue MSCs in the IR model of the rat brain.